Reintegration of child soldiers in Burundi: a tracer study - Jordans Mark JD; Komproe Ivan H; Tol Wietse A; Ndayisaba Aline; Nisabwe Theodora; Kohrt Brandon A (BMC, 2012)
Abstract Background Substantial attention and resources are aimed at the reintegration of child soldiers, yet rigorous evaluations are rare. Methods This tracer study was conducted among former child soldiers (N=452) and never-recruited peers (N=191) who participated in an economic support program in Burundi. Socio-economic outcome indicators were measured retrospectively for the period before receiving support (T1; 2005-06); immediately afterwards (T2; 2006-07); and at present (T3; 2010). Participants also rated present functional impairment and mental health indicators. Results Participants reported improvement on all indicators, especially economic opportunity and social integration. At present no difference existed between both groups on any of the outcome indicators. Socio-economic functioning was negatively related with depression- and, health complaints and positively with intervention satisfaction. Conclusion The present study demonstrates promising reintegration trajectories of former child soldiers after participating in a support program.